Range extension of the bat Lasiurus ega (Chiroptera: Vespertilionidae) in Honduras (UNED Research Journal, 2017)
In Honduras five species are known of the genus Lasiurus, we are presenting a range extension for Lasiurus ega in Honduras adding a new location in the department of Atlantida, also we are adding a new species to the list of mammals from the National Park ¨Nombre de Dios¨. The specimen comes from the El Cacao Lagoon. It was assigned to the species L. ega based in unique morphological characteristics as the color, teeth, total size and forearm size. Considering the little information that we have in Honduras about the Chiroptera group, is recommended to make systematics studies on this order nationwide
Keywords: Parque Nacional Nombre de Dios; FUPNAND; El Cacao Lagoon; Lasiurus ega; Honduras; Suthern Yellow Bat; Chiroptera; Insectivorus Bats.